Analisis Pengaruh PMA, PMDN dan Ekspor Migas-Nonmigas Terhadap Pertumbuhan Ekonomi Indonesia - Danita Lusi Kurniawati; Fitrah Sari Islami (Transpublika Publisher, 2022)
This study aims to analyze the effect of Foreign Investment, Domestic Investment, and Oil gas-Non oil gas Exports on Indonesia's economic growth. The data used is time series data from 2010 to 2019 on a quarterly basis. Data were analyzed using the ECM (Error Correction Model) method with the help of Eviews 10. The results showed that foreign investment and domestic investment had a significant effect in the short and long term on economic growth, while oil gas-non oil gas exports had no significant effect in the short and long term on economic growth.